172k views
0 votes
7 1/2 divided by -2 5/6

User Nixmind
by
5.2k points

1 Answer

2 votes


7\left((1)/(2)\right) /(-2)\left((5)/(6)\right) =
(45)/(-7) \text { or }-6.4285

Explanation:

Given expression:


7\left((1)/(2)\right) /(-2)\left((5)/(6)\right)


(7\left((1)/(2)\right))/((-2)\left((5)/(6)\right))

The fraction
7\left((1)/(2)\right) can be written by multiplying 7 with 2 and add to ‘1’. So,


7\left((1)/(2)\right)=(14+1)/(2)=(15)/(2)

The fraction
(-2)\left((5)/(6)\right) can be written by multiplying (-2) with 6 and add to ‘5’. So,


(-2)\left((5)/(6)\right)=(-12+5)/(6)=(-7)/(6)

Applying these, we get


((15)/(2))/((-7)/(6))

When do solving with numerator fraction, the denominator fraction
(-7)/(6) can be written as
(6)/(-7). Therefore,


(15)/(2) * (6)/(-7)=(15 * 3)/(-7)=(45)/(-7)=-6.4285

User Alexza
by
5.8k points